Assisting Economically Marginalized and Vulnerable Youth and Minimizing Opportunities for Exploitation by Adult Criminal Groups - Arnull, Elaine (Criminal justice and behavior, 2025)
This paper examines the exploitation of marginalized children and youth at risk of violent victimization and sexual exploitation by networks of adult criminals. Using the UK as an example, we consider various public inquiries that identified serious failings in UK criminal justice, social care, public health, and educational systems. These reports said that children and youth had been exploited by networks of adult criminals over time. They also described a sense of defeatism and lack of agency among the criminal justice and social service agencies to address the social, criminal, and public health problems associated with this form of child and youth exploitation. We discuss research that illuminates this issue and suggest some avenues for building trust between victims/survivors, community members, criminal justice agencies, and social services.